Respuesta :
To discover the values of the variables ( h and d ) we need first to isolate them in one side of the equation:
h + 13 = 7
To do that we can shift 13 to the other side of the equation by subtracting 13 from both sides of the equation:
h + 13 - 13 = 7 - 13
13 - 13 cancel out , so we end up with ;
h = - 6
Now the other equation :
d + ( - 9 ) = - 5
We need to do the same thing we did in the first equation , isolate the variable (d):
+ ( - 9 ) is the same thing as - 9 so our equation now is :
d - 9 = - 5
Shift - 9 to the other side by adding 9 tp both sides of the equation:
d - 9 + 9 = - 4 + 9
-9 + 9 cancel out so we end up with
d= 5
Awnser:
h = -6
d = 5
I hope you understood my brief explanation, and please consider marking this awnser as Branliest if you think it deserves it. Thank you! :)
h + 13 = 7
To do that we can shift 13 to the other side of the equation by subtracting 13 from both sides of the equation:
h + 13 - 13 = 7 - 13
13 - 13 cancel out , so we end up with ;
h = - 6
Now the other equation :
d + ( - 9 ) = - 5
We need to do the same thing we did in the first equation , isolate the variable (d):
+ ( - 9 ) is the same thing as - 9 so our equation now is :
d - 9 = - 5
Shift - 9 to the other side by adding 9 tp both sides of the equation:
d - 9 + 9 = - 4 + 9
-9 + 9 cancel out so we end up with
d= 5
Awnser:
h = -6
d = 5
I hope you understood my brief explanation, and please consider marking this awnser as Branliest if you think it deserves it. Thank you! :)